Coating thin film flows on a solid sphere - Taranets, R.M. (Нелінійні коливання, 2018)
By using the Arzelа – Ascoli theorem, we prove the existence of strong solutions of the thin film equation on a solid sphere in weighted Sobolev spaces. За допомогою теореми Арцела – Асколi доведено iснування сильних розв’язкiв рiвняння течiї тонкої плiвки на сферичнiй поверхнi у просторах Соболева з вагою.